An International Multicenter Prospective Study Evaluating the Long-term Oncological Impact of Adjuvant Chemotherapy in ypN+ Rectal Cancer. Issue 2 (28th February 2023) - Denost, Quentin; Fleming, Christina A.; Burghgraef, Thijs; Celerier, Bertrand; Geitenbeek, Ritchie; Rullier, Eric; Tuynman, Jurriaan; Consten, Esther; Hompes, Roel; ,
Abstract : Objective: To assess the oncological benefit of adjuvant chemotherapy (AC) in node positive (ypN+) rectal cancer after neoadjuvant chemoradiotherapy and radical surgery. Background: The evidence for AC after total mesorectal excision for locally advanced rectal cancer is conflicting and the net survival benefit is debated. Methods: An international multicenter comparative cohort study was performed comparing oncological outcomes in tertiary rectal cancer centers from the Netherlands and France. Patients with locally advanced rectal cancer treated with neoadjuvant chemoradiotherapy followed by total mesorectal excision surgery and with positive lymph nodes on histologic examination (ypN+) were included for analysis. Kaplan-Meier curves were generated to compare disease-free (DFS) and overall survival in AC and non-AC groups. Results: Of 1265 patients screened, a total of 239 rectal cancer patients with ypN+ disease were included. Demographic and clinical characteristics were similar in both groups. Higher systemic recurrence rates were observed in the non-AC group compared with those who received AC [32.0% (n=40) vs 17.5% (n=11), respectively, P =0.034]. DFS at 1 and 5 years postoperatively were significantly better in the AC group (92% vs 80% at 1 year; 72% vs 51% at 5 years, P =0.024), whereas no difference in overall survival was observed. Conclusions: In this multicenter comparative cohort study, we identified an oncological benefit of AC in both systemic recurrence and DFS in ypN+ rectal cancer patients. From this data, systemic chemotherapy continues to confer oncological benefit in locally advanced ypN+ rectal cancer.